IMPLEMENTASI KELAYAKAN ANGGARAN BUMDES DIKECAMATAN TAROWANG KABUPATEN JENEPONTO - Nasrullah .; Muhammad Nur Abdi; Sartina . (Jurnal Ilmiah Manajemen "E M O R", 2021)
The Village Fund allocation is very important in order to finance the development of disadvantaged areas in a development area system. The implementation of the Village Fund Allocation is aimed at physical and non-physical programs related to Village development indicators, which include education level, community income level, and health level. One of the rational reasons why there is a need for Village Fund Allocation (ADD) is because the village is positioned as the basis for decentralization. The ADD policy is very relevant to the perspective that places the village as the basis for participation, because the village is directly facing the community and community control is stronger.This study aims to determine the implementation of the Bumdes budget feasibility in accordance with the type of business program, and to determine the implementation of the Bumdes program in managing the budget allocated in the Tarowang sub-district, Jeneponto Regency.This research was obtained from several observations and interviews with related parties, this type of research is descriptive qualitative by selecting several informants. The data source used is the primary data source that is information sourced from direct observation of the research location by observation and interview. While secondary data sources are data sources obtained from documentation or literature studies to supplement primary data. Field research data collection through observation, interviews, and documentation. The results of this study indicate that the implementation of the Bumdes budget suitability in accordance with the type of business program in the Tarowang sub-district of Jeneponto district is considered feasible, but the implementation of the Bumdes program in managing the budget allocated in the Tarowang sub-district is less than optimal because of the lack of capabilities and human resource skills